Prediction of the Temperature of Large Framed Mold and Curing Deformation of Composite Components in the Autoclave Process - Zhipeng Wu; Anan Zhao; Ming Yue; Jungang Guo; Qing Wang; Yinglin Ke (Advances in Materials Science and Engineering)
The temperature uniformity and thermal deformation of the tool in the autoclave forming process have an important influence on the forming quality of the composite components. In this paper, the prediction methods of the temperature distribution of the tool and the curing deformation of composite components in the autoclave forming process were developed. Using Ansys CFX fluid analysis technology, the temperature field of a large framed tool in the autoclave process was simulated, and the distribution of the surface temperature of the large framed tool was obtained. The calculated temperature field was then applied in the cure-induced deformation simulation of composite components. The thermo-chemical-mechanical coupling analysis was conducted to simulate the curing deformation of the composite components, and the numerical results were verified by practical engineering application.